THE PROFILE OF THE PALESTINIAN SUICIDE MARTYRS (ISTISHHADIYIN) - Bassam Yousef Ibrahim Banat (European Scientific Journal, ESJ, 2015)
The Profile explores all the characteristics of the Palestinian suicide martyrs (Istishhadiyin) and the operations of their martyrdom as well. A national representative survey which consists of two-hundred participants of the Palestinian suicide martyrs (Istishhadiyin) families in the West Bank and Gaza Strip was used in this current Profile. The Palestinian suicide martyrs (Istishhadiyin) were able to implement two hundred qualitative martyrdom operations that rocked Israel, and raised a large wave of reactions both locally and internationally. The Profile has all their demographic characteristics; all the characteristics of their martyrdom operations; their personality characteristics mostly: social, religious, national and psychological features which qualified them to embark on this strategic action; also, the Profile has the main motivations which drove the Palestinian youth to carry out such operations, and the relationship between the emergence of these operations and Israeli crimes committed against the rights of the unarmed Palestinian people. Additionally, the Profile includes the main behavioral changes which appeared on the Palestinian suicide martyrs (Istishhadiyin) prior to the execution of the martyrdom operation, in addition to their families’ opinion about martyrdom operations. The Profile showed that the Palestinian suicide martyrs (Istishhadiyin) were ordinary people who enjoyed life; they were sociable, religious, national, and had a high degree of psychological stability. However, their motivations behind the carrying out of martyrdom operations are nationalistic, and are closely associated with the Israeli occupation of the Palestinian territories, and the daily suppressive practices against the helpless and unarmed Palestinian people. They had to sacrifice their lives for Palestinians, to shake off the occupation and preserve their holies, homeland, and people.